The impact of toxic parenting on children's emotional development - Sumiyati (Pusat Studi Gender dan Anak, 2024)
The way parents raise their children will have a significant impact on how they develop. Caregiving errors will result in toxic parenting, which will hinder the emotional growth of the child. Parents who have toxic parents are accustomed to speaking harshly, making fun of, demeaning, and even imposing their wishes on their kids. Many factors contribute to toxic parenting, such as past trauma experienced by the parents, personal issues they are facing, an inability to regulate their emotions, and excessive expectations placed on the parents for their children. There are various forms of toxic parenting, such as parents who make much effort to mold their kids into what they want them to be, parents who are dismissive of their kids and frequently make fun of them, and parents who are disdainful of their kids and frequently make fun of them. There are many impacts resulting from toxic parent behavior. Children who experience poisonous parents will have a low self-image, get stressed easily, be pessimistic, have difficulty controlling their emotions, worry, lack self-confidence, depression, and other emotional disorders, which will have an impact until the child is an adult. Thus, parents are responsible for protecting their children from negative parenting styles. Positive parenting can be used by parents who observe their children's behavior, provide opportunity and trust, manage their emotions, and maintain open lines of communication with their kids. All of this can improve children's development, especially their emotional development. Parents can reduce or even stop toxic parenting, among other things, by making peace with themselves, being grateful for all the little things they have, being willing to learn about correct parenting patterns, and, most importantly, realizing that children are a trust from the creator who will be held accountable.